The nexus between climate change, mobility, and conflict in Somalia - Abdullahi, Said; Singh, Radhika; Takaindisa, Joyce; Giacomelli, Camilla; Sax, Niklas; Carneiro, Bia; Pacillo, Grazia (2025)
This study explored the interplay between the climate, mobility, peace, and security (CMPS) nexus in Somalia, a country that has faced both climate extremes and protracted conflict in the past decades. It examined how climate change and variability impacted livelihoods, particularly through their effects on food, land, and water systems, and how these changes influenced social responses towards patterns of mobility, cooperation, and/or conflict. The study also analyzed how climate and conflict interact to drive displacement and the multifaceted challenges faced by displaced populations in the country. Regarding the methodology, search queries were formulated using terms related to climate, mobility, peace, and security, and were run on the Web of Science and Google Scholar databases, capturing a wide range of peer- reviewed papers. Results from both platforms were then merged to eliminate duplications. In addition, grey literature, including reports, briefs, and policy papers from climate security and migration research institutes, along with information from local and international news organizations, was incorporated to ensure an updated analysis. The study found that climate-related impacts contribute to economic hardship, poverty, and increased dependency on humanitarian aid in Somalia, eroding societal resilience. Rising temperatures, erratic rainfall, and droughts have disrupted pastoral and agricultural livelihoods, driving migration from rural areas and leading to one of the highest urbanization rates in the region. In addition, the study revealed that the convergent crises, namely climate and conflict, interact to drive displacement in the country. Displaced populations, particularly women and children, face increased vulnerability to gender-based violence and poor living conditions in overcrowded IDP camps. These populations strain urban infrastructure and disrupt established local clan dynamics and composition in the receiving areas, fueling tensions. Additionally, frequent and severe droughts have depleted pasture and created water stress, leading to deadly disputes over scarce resources among nomadic pastoralist clans. Finally, the study revealed how Al- Shabaab exploited and exacerbated climate- induced vulnerabilities, using blockades, taxation, and violence to control rural populations in regions already suffering from climate shocks. The study calls for targeted and context-specific interventions. It advocates for integrated strategies to bolster climate resilience through sustainable agricultural practices, urban planning for IDPs, and community-based conflict resolution mechanisms, particularly among nomadic pastoralists. By addressing these interconnected vulnerabilities, the study provides actionable insights for policymakers to mitigate the dual threats of climate change and conflict in Somalia.